1975
DOI: 10.1007/bf00285789
|View full text |Cite
|
Sign up to set email alerts
|

5-Methylcytosine in heterochromatic regions of chromosomes: chimpanzee and gorilla compared to the human

Abstract: Fixed metaphase chromosomes of gorilla and chimpanzee were UV-irradiated to produce regions of single-stranded DNA and then treated with antibodies specific for the minor DNA base 5-methylcytosine (5 MeC). An indirect immunofluorescence technique was used to visualize sites of antibody binding. In the gorilla six pairs of autosomes contained major fluorescent regions, indicating localized regions of highly methylated DNA. These corresponded, with the exception of chromosome 19, to the major regions of constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…No C-banding was found in the secondary constriction region of the comparable nucleolus organizing chromosome in the squirrel monkey, which is also a New World monkey (Ma et al, 1974), or in the rhesus macaque and African green monkeys, which are Old World monkeys (Stock and Hsu, 1973). However, in the more distantly related gibbon, Tantravahi et al (1975) found C-banding in the secondary constriction of the nucleolus organizing chromosome. In that case the chromosomes were frequently in association in this region, suggesting that the situation in the gibbon may be different from that in the monkeys.…”
Section: Discussionmentioning
confidence: 63%
“…No C-banding was found in the secondary constriction region of the comparable nucleolus organizing chromosome in the squirrel monkey, which is also a New World monkey (Ma et al, 1974), or in the rhesus macaque and African green monkeys, which are Old World monkeys (Stock and Hsu, 1973). However, in the more distantly related gibbon, Tantravahi et al (1975) found C-banding in the secondary constriction of the nucleolus organizing chromosome. In that case the chromosomes were frequently in association in this region, suggesting that the situation in the gibbon may be different from that in the monkeys.…”
Section: Discussionmentioning
confidence: 63%
“…The distribution of C5 methylated cytosine (5-MeC) in metaphase chromosomes has been studied in vertebrates, mainly in mammalian species, using immunolabeling with a polyclonal (Miller et al, 1974;Schnedl et al, 1975Schnedl et al, , 1976 or monoclonal (Miniou et al, 1994; antibody against 5-MeC. The results already obtained have shown a preferential binding of the antibody to heterochromatin-rich regions, whether the heterochromatin content is A+T or G+C, and the patterns produced by anti-5-MeC show heteromorphisms similar to those obtained with other staining methods.…”
mentioning
confidence: 73%
“…For example, the A-T-specific dye netropsin, which absorbs light only at wavelengths below those of 33258 Hoechst fluorescence (45), suppresses this fluorescence in all human chromosomes except for a few polymorphic regions (Fig. 5 A and B ) , which are also highlighted by immunochemical staining for 5-methylcytosine (26,27,39). This result, which is similar to that produced by 4',6-diamidinoindole and distamycin A (41), can be rationalized by a differential sensitivity of 33258 Hoechst and netropsin to pyrimidine C-5 substituents, as previously documented for Br (24,45).…”
Section: Resultsmentioning
confidence: 99%